1991
DOI: 10.1002/chin.199120013
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Thermodynamic Properties of (xCa + (1‐x)P)

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The temperature was measured with an EOP-66 optical pyrometer with an accuracy of +5 deg in the range 165031800 K. The instrument was preliminarily calibrated by CaF 2 vapor pressure [12,13]. The temperature was measured with an EOP-66 optical pyrometer with an accuracy of +5 deg in the range 165031800 K. The instrument was preliminarily calibrated by CaF 2 vapor pressure [12,13].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The temperature was measured with an EOP-66 optical pyrometer with an accuracy of +5 deg in the range 165031800 K. The instrument was preliminarily calibrated by CaF 2 vapor pressure [12,13]. The temperature was measured with an EOP-66 optical pyrometer with an accuracy of +5 deg in the range 165031800 K. The instrument was preliminarily calibrated by CaF 2 vapor pressure [12,13].…”
Section: Methodsmentioning
confidence: 99%
“…(11) The thermodynamic properties were determined at 1650 and 1730 K. The measured intensities of ion currents over the starting compositions of the samples allowed us to calculate the activity coefficients of BaO, B 2 O 3 , and SiO 2 by the procedure proposed in [8] and based on the Gibbs3Duhem equation. (12) and (13). For this reason, the partial pressure of atomic oxygen was replaced by the ratio of MoO 3 + and MoO 2 + ion currents, according to Eqs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since they have a high oxygen affinity, a mixture should also contain oxides at a certain proportion. The authors of [15] studied the thermodynamic properties using static measurement of the vapor pressure in the Ca-CaF 2 -CaO system and found that the use of Ca⎯CaF 2 -CaO mixtures with (mol %) 50-60 CaF 2 , 18-22 CaO, and 20-30 Ca makes it possible to decrease the calcium volatility severalfold and, thus, to decrease the calcium vapor losses at a retained flux extraction capacity with respect to copper.…”
mentioning
confidence: 99%